Genetic polymorphism of cytochrome P450 2D6 determines oestrogen receptor activity of the major infertility drug clomiphene via its active metabolites - Mürdter, Thomas E; Kerb, Reinhold; Turpeinen, Miia; Schroth, Werner; Ganchev, Boian; Böhmer, Gabriele M; Igel, Svitlana; Schaeffeler, Elke; Zanger, Ulrich; Brauch, Hiltrud; Schwab, Matthias (Human molecular genetics, 2012)
Clomiphene citrate is the most used drug for the treatment of female infertility, a common condition in western societies and developing countries. Despite dose escalation, up to 30% of women do not respond. Since clomiphene shares structural similarities with tamoxifen, which is predominantly bioactivated by the polymorphic cytochrome P450 (CYP) 2D6, we systematically explored clomiphene metabolism and action in vitro and in vivo by pharmacogenetic, -kinetic and -dynamic investigations. Human liver microsomes were incubated with clomiphene citrate and nine metabolites were identified by mass spectrometry and tested at the oestrogen receptor for their antagonistic capacity. (E)-4-hydroxyclomiphene and (E)-4-hydroxy-N-desethylclomiphene showed strongest inhibition of the oestrogen receptor activity with 50% inhibitory concentrations of 2.5 and 1.4 nm, respectively. CYP2D6 has been identified as the major enzyme involved in their formation using recombinant CYP450 isozymes as confirmed by inhibition experiments with CYP monoclonal antibodies. We correlated the CYP2D6 genotype of 30 human liver donors with the microsomal formation rate of active metabolites and observed a strong gene-dose effect. A healthy female volunteer study confirmed our in vitro data that the CYP2D6 polymorphism substantially determines the formation of the active clomiphene metabolites. Comparison of the C(max) of (E)-4-hydroxyclomiphene and (E)-4-hydroxy-N-desethylclomiphene showed 8 and 12 times lower concentrations in subjects with non-functional CYP2D6 alleles. Our results highlight (E)-4-hydroxyclomiphene and (E)-4-hydroxy-N-desethylclomiphene as the active clomiphene metabolites, the formation of which strongly depends on the polymorphic CYP2D6 enzyme. Our data provide first evidence of a biological rationale for the variability in the response to clomiphene treatment.